Utang Informal dan Kekerasan Berbasis Gender: Nikah Paksa sebagai Praktik Transaksional di Jawa Tengah - 'Ilma, Farichul (Asian Journal of Law and Humanity, 2025)
The right to choose a spouse is a fundamental principle in marriage. However, forced marriage remains prevalent in Indonesia, often driven by economic pressures. One such practice—forced marriage as a means of repaying parental debt—still occurs in Pakuncen, Wiradesa, Pekalongan, and serves as the focus of this study. This research aims to identify the underlying factors behind this practice and examine its legal implications from a socio-legal perspective. Employing empirical research with a socio-legal approach and a case study method, this study draws on both primary and secondary data collected through observation, interviews, and documentation. The findings reveal that urgent economic circumstances are a key driver of forced marriage for debt repayment in Pekuncen Village. This practice conflicts with Indonesian marriage law, which upholds free consent, and is not supported by Islamic law. It results in the loss of individual rights, disruption of family relationships, and perpetuation of gendered power imbalances. From a socio-legal perspective, these marriages illustrate how legal norms fail to function effectively when confronted by entrenched patriarchal culture and structural poverty. The study concludes that legal regulation alone is insufficient; meaningful solutions require social transformation, gender-sensitive mediation, and community empowerment to eradicate debt-driven forced marriage.